Evaluating the impact of IMO 2020 on the container shipping industry - Lutchman, Kavitha (Department of Commercial Law, 2022)
MARPOL Annex VI agreement (IMO 2020) entered into force in January 2020, seeking to reduce sulphur emissions in the global shipping industry arising from ships burning high sulphur bunker fuel. The regulation is estimated to cost the industry up to US$ 30 billion and offers no apparent direct benefit or advantage to the industry, as well as being ill-designed for effective enforcement. Shipowners who plan to comply have called for modifications to the regulation to address opportunities for non-compliance so that their good faith will not become a competitive disadvantage. These concerns around compliance are just one of the areas in which the efficacy of this regulation is being questioned. This paper takes a structured approach to assess the efficacy of this regulation in terms of four explicit goals: realising the necessary reduction in global sulphur emissions, achieving high compliance, encouraging continuous improvement in technology and business practices, and not unduly damaging the global shipping industry. These goals are assessed across five chapters, the first of which interrogates the legal framework of the regulation, exploring the complicated question of regulatory authority, with a special focus on the enforcement mechanisms and the catastrophic effect of the COVID-19 pandemic on basic enforcement processes. The next chapter investigates the likely impact on the industry, contrasting the impact of market-based regulations and control and command type regulations, and different tools such as permits and taxes. This chapter also discusses the emerging disagreement between developing and developed countries over who should be responsible for the costs of environmental reform. Next, a case study of A.P. Møller – Mærsk A/S (Maersk) explores the compliance experience of the largest shipping company in the world, including their internal structuring to deliver compliance, and their pricing adjustments to offset some of the costs. The following chapter evaluates the practical and economic costs of this regulation across all major elements of the global shipping industry. The penultimate chapter makes an effort to predict what the long-term impact of this regulation is likely to be, using two different models for evaluating the interactions between profit-seeking industries and new environmental regulations in general: the Porter Hypothesis and the Polluter Haven Hypothesis. The final chapter concludes the paper with an evaluation of the regulation, and some suggested next steps which could improve the likelihood that the long-term goals of IMO 2020 will be realised.